2017
DOI: 10.1111/irv.12453
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of influenza and respiratory syncytial virus incidences with fraction modeling approach in Baguio City, the Philippines, 2012‐2014

Abstract: BackgroundEstimation of the incidences of influenza and respiratory syncytial virus (RSV) infection is important for disease control. Previous estimate in the city showed a substantial burden of influenza in both outpatients and inpatients while it did not account for individuals who do not seek medical attention nor RSV.Patients/MethodsA total of 17 674 influenza‐like illness (ILI) and 13 242 severe acute respiratory illness (SARI) cases were recruited, and samples were collected from 6267 and 2962 of ILI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…The overall burden of RSV among health-seeking populations has mostly been evidenced in young children, adults above 65 years of age, pregnant women or immunocompromised patients in whom equivalent disease burden to influenza has been reported [ 19 21 ]. The estimation of severe RSV infections in Switzerland is limited by the lack of an active RSV surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…The overall burden of RSV among health-seeking populations has mostly been evidenced in young children, adults above 65 years of age, pregnant women or immunocompromised patients in whom equivalent disease burden to influenza has been reported [ 19 21 ]. The estimation of severe RSV infections in Switzerland is limited by the lack of an active RSV surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent surveillance across the Philippines consistently shows RSV ranking as one of the top two most commonly detected respiratory viruses each year, and as the leading cause of hospitalization among infants and young children [ 25 , 26 , 27 , 37 , 38 , 39 , 40 ]. Furuse et al found that nearly 24% of all RSV-infected children visit a medical facility during their infection, with 2% requiring hospitalization [ 38 ].…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
“…In Baguio City (population ~350,000; elevation 4800 ft), the average RSV incidence rates are reported at 1.4 per 1000 individuals, with the highest age-group-specific incidence rates of 21.7–38 per 1000 individuals occurring in infants 6–23 months of age [ 40 ]. Among children less than 6 mos of age, mean hospitalization rates for RSV were between 2 and 8-fold higher than for influenza.…”
Section: Rsv Disease Activity Across Tropical Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Although the highest number of cases overall was associated with influenza A, most cases of RSV, adenoviruses, B. pertussis , and enteroviruses occurred in children less than ten years old. These organisms were previously reported to be most common among children [ 15 18 ]. Further, RSV had the highest incidence among children less than 5 years old, but another increase in RSV hospitalization rates was observed among elderlies (≥60 years old).…”
Section: Discussionmentioning
confidence: 99%